Delimiting spheres of influence of Gweru and their role in the development planning of the Midlands Province of Zimbabwe - Jerie, Steven (Organisation For Social Science Research In Eastern And Southern Africa, 2016)
This study aims at identifying the service areas of Gweru and other settlements in the Midlands province of Zimbabwe. This is because a close relationship exists between any settlement and the countryside around it. The delimitation of service areas is based on the study of the economic, social and administrative functions offered by the central places. Questionnaires and interviews were used to gather data from the authorities of these functions. Secondary data sources were also used and these included topographic maps, bus timetables, daily and weekly newspapers, published papers and reports from the Central Statistical Office (CSO). Reilly’s Law of Retail Gravitation was also employed as a statistical method to test against the empirical method. It was established that the sphere of influence of Gweru is mostly concentrated about the Midlands Province and it is not hexagonal in shape as predicted by Walter Christaller for most service areas. The distortions in shape are due to several factors that include competition from other centres, elongation along transport routes, the impact of administrative boundaries and other truncation factors. The hierarchy of settlements formed is an unbalanced one with two dominant grade 6 centres, Gweru and Kwekwe, and it shows lack of settlements in the middle orders. This situation is typical of a primate settlement hierarchy. Service area study is vital in development planning of the Midlands Province as it assists in identifying those areas of the region that are lacking in terms of service provision.